Analisis dan Evaluasi Infrastruktur Jaringan di SMA Negeri 3 Tasikmalaya - Dardha, Muhamad Yusa; Ikhlas, Andri Nur; Dzulfikar, Helmy (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
This study aims to analyze and evaluate the computer network infrastructure at SMA Negeri 3 Tasikmalaya, which highly depends on an internet connection for school operational activities, such as Dapodik, Computer Based Test (CBT) exams, and e-Raport. Although the school has implemented a dual ISP architecture, allocating the Indibiz line for Administration and a 100 Mbps iForte line for teachers and students, users frequently experience network performance degradation or bottlenecks during peak hours. Furthermore, wireless signal coverage currently reaches only 60%, resulting in the emergence of blank spot areas. Network performance evaluation was conducted using Quality of Service (QoS) parameters based on TIPHON standards. The analysis results indicate that during peak hours, the throughput value falls into the "Poor" category due to the absence of an adaptive bandwidth management system to handle hundreds of users. Issues regarding physical device stacking and security vulnerabilities resulting from a malware attack incident on the virtual server were also discovered. This study recommends implementing bandwidth management using the Per Connection Queue (PCQ) method on Mikrotik, restructuring and adding Access Points, as well as enhancing active network security and monitoring systems.